Microinjection of alpha-MSH followed by UV-irradiation blocks HSP 72 in human keratinocytes - Held, Björn; Amato, Susanne; Jung, Ernst G.; Bayerl, Christiane (Annals of the New York Academy of Sciences, 1999)
The aim of this study was to investigate the interaction of alpha-melanocyte-stimulating hormone (α-MSH) and heat shock protein 72 (HSP 72) in human keratinocytes in order to learn about the link between the neuroimmunocutaneus system and UV-induced immunomodulation. 1-3α-MSH, a proopiomelanocortin (POMC) derived neuropeptide, 4 is produced in human keratinocytes 5, 6 as well as in normal and pathologic human skin. 7 It is upregulated by UV-irradiation, 8 and it is a potent mediator of inflammation 9, 10 and immune response. 3, 11 HSP 72, a chaperoning protein that has protective properties on cells, 12, 13 is upregulated by environmental stresses such as heat, UV-irradiation, drugs, and chemicals. 12, 14 Orel et al., 13 showed that there are inverse interactions between α-MSH and HSP 72 in the HaCat cell line. Therefore, we microinjected α-MSH into primary human keratinocytes in culture so as to study changes in HSP 72 at the protein level.
Elektronische Reproduktion der Druck-Ausgabe
First published: 06 February 2006
Gesehen am 23.05.2022